Impact of Sagittal Balance on Clinical Outcomes in Surgically Treated T12 and L1 Burst Fractures: Analysis of Long-Term Outcomes after Posterior-Only and Combined Posteroanterior Treatment. (10th January 2017) - Mayer, M.; Ortmaier, R.; Koller, H.; Koller, J.; Hitzl, W.; Auffarth, A.; Resch, H.; von Keudell, A.
Abstract : Objective . Long-term radiological and clinical outcome retrospective study of surgical treatment for T12 and L1 burst fractures in perspective of sagittal balance measures. Methods . Patients with age of 16–60 years, complete radiographs, early surgical treatment surgery, and follow-up (F/U) > 18 months were included and strict exclusion criteria applied. Regional and thoracolumbar kyphosis angles (RKA and TLA) were measured preoperatively and at final F/U, as were parameters of the spinopelvic sagittal alignment. Clinical outcomes were assessed using validated measures. Results . 36 patients with age mean age of 39 years and F/U of 69 months were included. 61% of patients were treated with bisegmental posterior instrumentation (POST-I) and 39% with combined posteroanterior instrumented fusion (PA-F). At F/U, several indicators for clinical outcomes showed a significant correlation with radiographic measures in the overall cohort with inferior clinical outcomes corresponding with increasing residual deformity and sagittal malalignment. Statistical analysis failed to reach level of significance for the differences between POST-I and PA-F group at final F/U. Only a strong trend towards better restoration of the thoracolumbar alignment was observed for the PA-F group in terms of the RKA and TLA. Conclusions . Results in a surgically treated cohort of T12 and L1 burst fracture patients indicate that superior clinical outcomes depend on restoration of sagittal alignment.